Modeling Coral Reef Fish Home Range Movements in Dry Tortugas, Florida. (16th January 2014) - Farmer, Nicholas A.; Ault, Jerald S.
Abstract : Underestimation of reef fish space use may result in marine reserves that are too small to effectively buffer a portion of the stock from fishing mortality. Commonly used statistical home range models, such as minimum convex polygon (MCP) or 95% kernel density (95% KD) methods, require the exclusion of individuals who move beyond the bounds of the tracking study. Spatially explicit individual-based models of fish home range movements parameterized from multiple years of acoustic tracking data were developed for three exploited coral reef fishes (red grouper Epinephelus morio, black grouper Mycteroperca bonaci, and mutton snapper Lutjanus analis ) in Dry Tortugas, Florida. Movements were characterized as a combination of probability of movement, distance moved, and turning angle. Simulations suggested that the limited temporal and geographic scope of most movement studies may underestimate home range size, especially for fish with home range centers near the edges of the array. Simulations provided useful upper bounds for home range size (red grouper: 2.28 ± 0.81  km 2 MCP, 3.60 ± 0.89  km 2 KD; black grouper: 2.06 ± 0.84  km 2 MCP, 3.93 ± 1.22  km 2 KD; mutton snapper: 7.72 ± 2.23  km 2 MCP, 6.16 ± 1.11  km 2 KD). Simulations also suggested that MCP home ranges are more robust to artifacts of passive array acoustic detection patterns than 95% KD methods.